Prevalence, awareness, treatment and control of hypertension in Greece: EMENO national epidemiological study. Issue 5 (25th May 2021) - Stergiou, George S.; Menti, Ariadni; Kalpourtzi, Natasa; Gavana, Magda; Vantarakis, Apostolos; Chlouverakis, Grigoris; Hajichristodoulou, Christos; Trypsianis, Grigoris; Voulgari, Paraskevi V.; Alamanos, Yannis; Karakosta, Argiro; Touloumi, Giota
Abstract : Objective: The evidence on the epidemiology of hypertension in Greece is limited. The prevalence and control of hypertension was assessed in randomly selected adults of the general population in Greece within the nationwide epidemiological study EMENO. Method: On the basis of 2011 census, EMENO applied a multistage stratified random sampling method involving 577 areas throughout Greece (2013–2016). Participants were assessed at home visits with standardized questionnaires, blood tests and triplicate seated blood pressure (BP) measurements (validated upper-arm automated oscillometric device Microlife BPA100 Plus). Hypertension was defined as BP at least 140/90 mmHg (average of second–third measurement) and/or use of antihypertensive drugs. Sampling weights were applied for study design and post-stratification weights to match the age/sex distribution to the general population in Greece. Nonresponse was adjusted by inverse probability weighting. Results: A total of 6006 individuals were recruited and 4699 with valid data were analysed [mean (SD) age 49.2 (18.6) years, men 48.6%, BMI 28.2 (5.7) kg/m 2 ]. The prevalence of hypertension was 39.6% and was higher in men than women (42.7 vs. 36.5%, P < 0.001). Among patients with hypertension, 31.8% were unaware (men/women 39.2/23.6%, P < 0.001), 2.7% aware but untreated (men/women 2.9/2.5%, P = NS), 35.1% treated uncontrolled (32.1/38.3%, P < 0.01) and 30.5% treated controlled (25.8/35.6%, P < 0.001). Conclusion: The prevalence of hypertension in Greece seems to be rising and affects 40% of the adults. One-third of them are undiagnosed and only 30% are controlled with treatment. Nationwide programmes are needed to prevent hypertension and improve its awareness and control aiming at reducing the rate cardiovascular diseases.